2012
DOI: 10.1186/ar3852
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of rhythms of molecular clocks in primary synovial fibroblasts of patients with osteoarthritis and rheumatoid arthritis, role of IL-1β/TNF

Abstract: IntroductionCircadian rhythms play an important role in the body and in single cells. Rhythms of molecular clocks have not been investigated in synovial fibroblasts (SF) of patients with osteoarthritis (OA) and rheumatoid arthritis (RA). The study was initiated to fill this gap and to study effects of interleukin (IL)-1β/tumor necrosis factor (TNF) on rhythmicity in synovial fibroblasts of RA and OA patients.MethodsThe presence of BMAL-1, CLOCK, Period 1 and Period 2 proteins in synovial tissue was investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 41 publications
3
53
0
Order By: Relevance
“…Evidence demonstrated mice with mutant clock genes exhibited altered regulation of bone volume (8) and increasing susceptibility to inflammatory arthritis (10). Previous study showed expression of clock protein or gene in synovial tissue and cells from OA and RA patients (34), however, no studies have addressed how clock genes changed in articular cartilage of patients with OA.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence demonstrated mice with mutant clock genes exhibited altered regulation of bone volume (8) and increasing susceptibility to inflammatory arthritis (10). Previous study showed expression of clock protein or gene in synovial tissue and cells from OA and RA patients (34), however, no studies have addressed how clock genes changed in articular cartilage of patients with OA.…”
Section: Discussionmentioning
confidence: 98%
“…55,58 Additionally, TNF-α and IL-1β can suppress the expression of the circadian gene Per as well as the clock-controlled genes D site of albumin promoter [albumin D-box]-binding protein ( Dbp ), thyrotroph embryonic factor (Tef ), and hepatic leukemia factor ( Hlf ). 61,62 Haas and Straub 25 also found that TNF-α inhibited the expression of Clock , Per1 , and Per2 in synovial tissue cells isolated from osteoarthritis patients, whereas TNF-α and IL-1β increased the expression of these genes in RA synoviocytes. 25 Persistent disruption of the circadian rhythms has been closely associated with diseases in which chronic inflammation is among the principal pathological features, 63 and elements of the immune system implicated in the chronic inflammation have been shown to be under circadian control.…”
Section: Regulation Of Cytokines and Oxidative Stress Response Bmentioning
confidence: 92%
“…61,62 Haas and Straub 25 also found that TNF-α inhibited the expression of Clock , Per1 , and Per2 in synovial tissue cells isolated from osteoarthritis patients, whereas TNF-α and IL-1β increased the expression of these genes in RA synoviocytes. 25 Persistent disruption of the circadian rhythms has been closely associated with diseases in which chronic inflammation is among the principal pathological features, 63 and elements of the immune system implicated in the chronic inflammation have been shown to be under circadian control. Kouri et al 64 found clock gene expression to be disrupted in synoviocytes isolated from RA patients, with increased expression of REV-ERBα and the relative phase differences between BMAL1 and PER1 to be altered.…”
Section: Regulation Of Cytokines and Oxidative Stress Response Bmentioning
confidence: 92%
See 1 more Smart Citation
“…These clocks regulate the circadian rhythms of inflammatory innate immune functions [13, 14]. Recently, Haas and Straub [15] described daily Bmal1 and Per1 rhythms in synovial fibroblasts of healthy subjects. Expression of clock proteins and their transcripts such as Bmal1 , Clock , Per1 , and Per2 has also been reported in synovial cells and tissues of patients with osteoarthritis and RA [16].…”
Section: Introductionmentioning
confidence: 99%